2010
DOI: 10.3390/ph3092970
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Engineering of Cartilage; Can Cannabinoids Help?

Abstract: This review discusses the role of the cannabinoid system in cartilage tissue and endeavors to establish if targeting the cannabinoid system has potential in mesenchymal stem cell based tissue-engineered cartilage repair strategies. The review discusses the potential of cannabinoids to protect against the degradation of cartilage in inflamed arthritic joints and the influence of cannabinoids on the chondrocyte precursors, mesenchymal stem cells (MSCs). We provide experimental evidence to show that activation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 79 publications
(104 reference statements)
1
7
0
Order By: Relevance
“…Thus, Δ 9 -THC exposure may lead to a decreased ability of MSCs to differentiate into their mature bone forming progeny due to a lack of cell viability at early stages of osteogenesis which could inturn impact upon the osteogenic potential of MSCs (supplemental Figure  4). Furthermore we conclude that this effect is specific to a long-term treatment with Δ 9 -THC as we have previously published observations showing no deleterious effects following an acute 24-hour Δ 9 -THC (1  μ M) treatment [29]. This indicates that a long-term exposure to Δ 9 -THC may have a negative effect on bone health possibly due to exogenous agonist-induced blockade of CB 1 receptor activation by endocannabinoids.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Thus, Δ 9 -THC exposure may lead to a decreased ability of MSCs to differentiate into their mature bone forming progeny due to a lack of cell viability at early stages of osteogenesis which could inturn impact upon the osteogenic potential of MSCs (supplemental Figure  4). Furthermore we conclude that this effect is specific to a long-term treatment with Δ 9 -THC as we have previously published observations showing no deleterious effects following an acute 24-hour Δ 9 -THC (1  μ M) treatment [29]. This indicates that a long-term exposure to Δ 9 -THC may have a negative effect on bone health possibly due to exogenous agonist-induced blockade of CB 1 receptor activation by endocannabinoids.…”
Section: Discussionsupporting
confidence: 84%
“…Furthermore, they showed that increased CB 1 receptor expression enhanced the efficacy of cannabinoids to regulate the prosurvival AKT pathway whilst low levels of CB 1 receptor expression lead only to the activation of ERK [28]. Furthermore, we have previously shown that activation of the cannabinoid system enhances the survival, migration, and chondrogenic differentiation of MSCs, which are the three key points that determine the success of cell-based tissue-engineered repair strategies [29]. Interestingly, Idris et al [13] suggest that normal bone formation in CB 1 receptor knock-out mice can be maintained by alternative signalling pathways; however, with increasing age these compensatory mechanisms fail leading to decreased bone formation.…”
Section: Discussionmentioning
confidence: 99%
“…There is a consensus in all studies conducted on the effect of cannabis on the induction of apoptosis, but all have overlooked the role of the dose (2,3,5,7,11,21,22). But some people have said that the delta-9-tetrahydrocannabinol in the extract acts as an antioxidant for cell viability, while at the same time high concentrations of this substance cause toxicity and increase apoptosis (9).…”
Section: Discussionmentioning
confidence: 99%
“…Cannabinoids (CBs) have been reported to have analgesic, anti‐inflammatory, and immunosuppressive effects in animal models of arthritis 45. These positive influences help protect against cartilage degradation in inflamed arthritic joints and osteoarthritis 46, 47. Chondrocytes maintain cartilage tissue homeostasis, sustaining the crucial balance between the rate of biosynthesis and incorporation of matrix components, and the rate of their degradation and subsequent loss from the cartilage into the synovial fluid 48.…”
Section: Discussionmentioning
confidence: 99%